2014
DOI: 10.1038/nm.3737
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo model of human small intestine using pluripotent stem cells

Abstract: Differentiation of human pluripotent stem cells (hPSCs) into organ-specific subtypes offers an exciting avenue for the study of embryonic development and disease processes, for pharmacologic studies and as a potential resource for therapeutic transplant1,2. To date, limited in vivo models exist for human intestine, all of which are dependent upon primary epithelial cultures or digested tissue from surgical biopsies that include mesenchymal cells transplanted on biodegradable scaffolds3,4. Here, we generated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
583
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(605 citation statements)
references
References 32 publications
18
583
0
4
Order By: Relevance
“…Spence et al have shown that a sequential differentiation program can guide both mice ES cells and iPS cells to endoderm progenitors, and subsequently to IECs [125]. Such an in vivo induction of pluripotent cells towards intestinal tissues is also possible in human ES cells or iPS cells, and those engineered intestinal tissues are validated to have a satisfying level of intestine-specific functions [126]. A comprehensive search for transcription factors that are required for endodermal differentiation has revealed that so-called ''iHep cells'' are able to form intestinal organoids, and can be transplanted onto the damaged colonic epithelium [127].…”
Section: Iecs As Target Cells For the Treatment Of Ibdmentioning
confidence: 99%
“…Spence et al have shown that a sequential differentiation program can guide both mice ES cells and iPS cells to endoderm progenitors, and subsequently to IECs [125]. Such an in vivo induction of pluripotent cells towards intestinal tissues is also possible in human ES cells or iPS cells, and those engineered intestinal tissues are validated to have a satisfying level of intestine-specific functions [126]. A comprehensive search for transcription factors that are required for endodermal differentiation has revealed that so-called ''iHep cells'' are able to form intestinal organoids, and can be transplanted onto the damaged colonic epithelium [127].…”
Section: Iecs As Target Cells For the Treatment Of Ibdmentioning
confidence: 99%
“…Growth, in response to massive small bowel resection, was noted in the kidney capsule in an in vivo implant model. There was no evidence presented for an ENS (Watson et al 2014).…”
Section: Tissue Engineering Functional Gastrointestinal Regionsmentioning
confidence: 90%
“…Pluripotent stem cells have been developed into many of the components of functional intestine, although development of an innervated smooth muscle layer is missing and immunosuppression would be required (Watson et al 2014).…”
Section: Small Intestinementioning
confidence: 99%
“…Transplanted human intestinal organoids have displayed mature intestine characteristics such as peptide uptake, but therapeutic application would require additional functions, such as the ability to perform the peristaltic movements essential for food bolus transition along the digestive tract [48].…”
Section: Organoid Disease Modeling and Transplantationmentioning
confidence: 99%